Sulfites: Separating Fact from Fiction - Paul Grotheer; Maurice Marshall; Amy Simonne (EDIS)
If you have a strong allergic reaction to sulfites you may already know some ways to avoid the substances. However, even with today's technology, food recalls due to undeclared sulfite (as a food ingredient) continue to occur in the United States. This publication will examine what sulfites are, sulfite sensitivity, safety issues related to sulfiting agents, and recommendations for sulfite-sensitive individuals. This document is FCS8787, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 2005.